MULTI-COLOUR CYTOMETRIC ANALYSIS. IDENTIFICATION OF T LYMPHOCYTES AND THEIR SUBSETS - S. V. Khaidukov; A. V. Zurochka; V. A. Chereshnev (Медицинская иммунология, 2014)
Abstract. T-lymphocytes play an important role in elimination of tumor cells, in reactions of a transplant against graft and graft versus host disease, in slow-type hypersensitivity, and other reactions directed for maintenance of homeostasis. Along with CD3, an antigen-specific T-cellular receptor (TCR) is another common marker of T-cells. There are two types of TcR – αβ-TcR and γδ-TcR that differ in ontogenetic and functional properties. γδ-T-cells play a significant role in protection of organism against various types of infections, and determination of their amounts should be an integral part of the analysis of patients’ immune status. To these purposes, a multi-colour analysis shuld be used, applying the following combinations of monoclonal antibodies: CD3/CD4/CD8/CD45 and αβ-TcR/γδ-TcR/CD3/CD45. Multi-colour staining and multi-step gating allow of carrying out multiparametric analysis of peripheral blood with high accuracy and reliability. The proposed approach considerably facilitates interpretation of results obtained, and it allows of judging about immune system functioning in various pathological conditions.